POEM OF TARAS SHEVCHENKO «TARASOVA NIGHT» AND «HISTORY OF RUS'»: SIMILARITIES AND DIFFERENCES - Nykyforiuk, A. Yu. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
Taras Shevchenko’s life was for his motherland and his talent was for her, and even time and authority couldn’t trample his name in unknown quantity. Memory about this great men life in our harts and our thoughts. Poems T.S. Shevchenkо “Tarasova night” to tie with “‘Istoria rusiv”. Main object to concentrate on image T. Trasulo. Describe his actions deed and consequence.